2022
DOI: 10.3233/adr-220001
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Mechanism of β-Asarone on Improving Cognitive Dysfunction in Rats with Diabetic Encephalopathy

Abstract: Background: The number of people with diabetes is increasing, and many patients have significantly impaired cognitive function. For patients with diabetic encephalopathy (DE), simply lowering blood sugar does not improve learning and memory. Studies have shown that β-asarone can significantly improve cognitive impairment in patients with DE, but the specific mechanism of action is unclear. Objective: This experiment hopes to use a variety of experimental methods to clarify the protective effect and mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, β-asarone blocked the activation of NF-κB by HG and decreased the production and expression of IL-1β and IL-18, which are pro-inflammatory cytokines associated with NLRP3 inflammasome activation [15,16]. β-asarone inhibits HG-induced NLRP3 inflammasome activation in a myocardial I/R model [23]. These results imply that β-asarone protects ARPE-19 cells from HG-mediated oxidative stress, inflammation, and apoptosis via the regulation of NF-κB-related pathways.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, β-asarone blocked the activation of NF-κB by HG and decreased the production and expression of IL-1β and IL-18, which are pro-inflammatory cytokines associated with NLRP3 inflammasome activation [15,16]. β-asarone inhibits HG-induced NLRP3 inflammasome activation in a myocardial I/R model [23]. These results imply that β-asarone protects ARPE-19 cells from HG-mediated oxidative stress, inflammation, and apoptosis via the regulation of NF-κB-related pathways.…”
Section: Discussionmentioning
confidence: 92%
“…Even with toxicological effects of β-asarone, it demonstrates therapeutic properties by targeting various pharmacological molecular targets such as apoptotic pathway modulator [20]. In particular, the antioxidant activity of β-asarone is related to the quenching of ROS generation in various experimental systems, including Alzheimer's disease and diabetic encephalopathy models [23,45,46]. Chang and Teng [47] reported that β-asarone inhibits the production of inflammatory cytokines, including tumor necrosis factor-α (TNF-α), IL-1β, and IL-6, and induction of autophagy, while reducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation